CONTRIBUTION OF OZONE TO ADAPTATION PROCESSES TO HYPOXIA (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
The evaluation of the features of the erythrocyte response to the action of ozone inexperiments in vitro was carried out. An increase in the effect of this gas on the parameters of oxygentransport in a suspension of erythrocytes was revealed, which is more pronounced with the addition of adonor of gas-transmitter nitrogen monoxide (nitroglycerin) and is not observed with the introduction ofhydrogen sulfide.Incubation of erythrocyte suspension with ozone causes the development of oxidativestress, which is manifested by an increase in the concentrations of diene conjugates, malondialdehyde, and adecrease in catalase activity, which indicates an overload of antioxidant defense mechanisms. Nitroglycerinand sodium hydrosulfide do not change the activating effect of ozone on the processes of free radicaloxidation, however, they activate the enzymatic link of the antioxidant defense catalase.
Keywords: erythrocytes, ozone, gas transmitter, nitrogen monoxide, hydrogen sulfide.